Product Quality and Variety as Determinants of Purchase Decisions: The Moderating Role of Price in Herbalife Market, Ubud Indonesia - Putu Ayu Titha Paramita Pika; Ni Komang Indra Swari; Nyoman Sri Subawa (Amkop Management Accounting Review (AMAR), 2026)
The wellness industry in Indonesia is experiencing significant growth, driven by increasing consumer awareness of health, nutrition, and a holistic lifestyle. This study aims to analyze the influence of product quality and product variety on Herbalife purchasing decisions in Ubud, Bali, with price as a moderating variable. The research approach used was quantitative, with proportionate stratified random sampling of 100 Herbalife consumers in Ubud. Data were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) through SmartPLS 4.1 to test for direct and moderating effects. The results showed that. Product quality had a positive and significant effect on Herbalife purchasing decisions in Ubud. Product variety had no significant effect on Herbalife purchasing decisions in Ubud. Price had a positive and significant effect on Herbalife purchasing decisions in Ubud. Product quality had a significant effect on purchasing decisions through price moderation. Product variety had a significant effect on purchasing decisions through price moderation.